Analysis of the Mechanism of Ureproofing Technology and Postlaparoscopy on Patients with Urology and Infection. (21st April 2022) - Chen, Si; Zhang, Yuanfeng; Shen, Peilin; Huang, Zhuangcheng; Lin, Mingen; Huang, Jiansheng
Abstract : Objective . To analyze the effect of ureteroscopy and retrolaparoscopy on urinary calculi and infection. Method . A total of 64 patients with urinary calculi and infection who received treatment in our hospital from June 2018 to January 2018 were selected. According to the different treatment methods, they were divided into two groups: a control group and a study group. The study group was treated with laparoscopic ureteroscopy, and the control group was treated with ureteroscopy. The surgical results, complications, renal function, stress response, and inflammatory reaction were compared between the two groups. Results . Compared with the control group, the study group stone clearance rate was higher, the surgical time was shorter P < 0.05 ; the incidence of complications in the study group (23.3%) was lower than that in the control group (5.9%) P < 0.05 ; there was no significant difference in kidney function indicators before treatment P > 0.05 ; after treatment, the SCR, BUN, NGAL, and Cys-C indicators of the two groups were significantly increased. Compared with the control group, the study group change was more obvious, and the difference was statistically significant P < 0.05 ; after treatment, the two sets of stress response indicators were significantly increased, but relative to the control group, the study group stress response indicator was lower P < 0.05 ; before treatment, there was no significant difference in inflammatory factors P > 0.05 ; after treatment, the two sets of inflammatory factor levels were significantly increased, but relative to the control group, the study group was lower P < 0.05 . Conclusion . In the clinical treatment of urinary stones, ureteroscopy technology and the laparoscopic technique have played an important role. But the laparoscopic technique is shorter, the stone clearance is higher, and the patient's renal function can be improved, and the patient is postoperative. The stress reaction should be small. Therefore, in the clinical treatment of urinary stones and infection, laparoscopic technical treatment is worth promoting.